2019
DOI: 10.3758/s13428-019-01321-2
|View full text |Cite
|
Sign up to set email alerts
|

Mental chronometry in the pocket? Timing accuracy of web applications on touchscreen and keyboard devices

Abstract: Web applications can implement procedures for studying the speed of mental processes (mental chronometry) and can be administered via web browsers on most commodity desktops, laptops, smartphones, and tablets. This approach to conducting mental chronometry offers various opportunities, such as increased scale, ease of data collection, and access to specific samples. However, validity and reliability may be threatened by less accurate timing than specialized software and hardware can offer. We examined how accu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 32 publications
(56 reference statements)
5
34
0
Order By: Relevance
“…These differences are potential reasons for the different data we report. Researchers should keep these instances of larger delays in mind when conducting reaction-timesensitive studies, by ensuring relative RTs are used (Pronk et al, 2019;Bridges et al, 2020). When timing sensitivity is crucial, we recommend employing within-participant designs where possible to avoid having to make comparisons between participants with different devices, operating systems, and browsers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These differences are potential reasons for the different data we report. Researchers should keep these instances of larger delays in mind when conducting reaction-timesensitive studies, by ensuring relative RTs are used (Pronk et al, 2019;Bridges et al, 2020). When timing sensitivity is crucial, we recommend employing within-participant designs where possible to avoid having to make comparisons between participants with different devices, operating systems, and browsers.…”
Section: Discussionmentioning
confidence: 99%
“…There have been various claims made on the scientific record regarding the display and response timing ability of experimental set-ups using web browsers-for instance, that timing can be good depending on device and set-up (Pronk, Wiers, Molenkamp, & Murre, 2019), and that different techniques for rendering animations lead to reduced timing precision (Garaizar & Reips, 2019). Ultimately, though, the variance in timing reflects the number of different ways to create an online experiment, and the state of the software and hardware landscape at the time of assessment-all of these are changing at a fast rate.…”
Section: The Current Statementioning
confidence: 99%
See 2 more Smart Citations
“…In general, latencies and variabilities are higher in web-based compared to lab-environments. Several studies have assessed the quality of timing in online studies, with encouraging results (Anwyl-Irvine, Dalmaijer, et al, 2020;Bridges et al, 2020;Pronk et al, 2019;Reimers & Stewart, 2015). An online evaluation of a masked priming experiment showed that very short stimulus durations (i.e., under 50ms) can be problematic (but see Barnhoorn et al, 2014), but other classic experimental psychology paradigms that rely on reaction times (e.g., Stroop, flanker, and Simon tasks)…”
Section: Frequently Asked Questionsmentioning
confidence: 99%